A polymer-based probe for specific discrimination of cysteine. Issue 22 (24th May 2017) - Liu, Keyuan; Du, Ganhong; Zhao, Mengna; Ye, Long; Shen, Huifang; Jiang, Liming
Abstract : A kind of polymer-based turn-on fluorescent probe for specific detection of cysteine with high sensitivity has been developed. Abstract : A novel optically active methacrylic polymer with an amide-linked acrylate appendage as a chemosensor was synthesized by atom transfer radical polymerization (ATRP) followed by post-modification through a bottom-up design. The sensing behavior of the polymeric probe to various α-amino acids has been investigated through fluorescence, absorption, circular dichroism (CD), and visual color changes at physiological pH. It was found that the sensor exhibits specificity for the fluorescent recognition of cysteine against other amino acids and thiols in a turn-on mode, being significantly more effective than the corresponding small molecule counterpart. The detection limit was estimated to be in the micromolar range. In addition, the use of this chiral polymer allows the selective discrimination of cysteine enantiomers based on either fluorescence or CD spectral responses. Interestingly, the cysteine assay could also be visualized by the naked eye in the presence of small amounts of ferric ions.